SARS-CoV-2 Infection as a Possible Trigger for IgA-Associated Vasculitis: A Case Report - Edyta Machura; Helena Krakowczyk; Katarzyna Bąk-Drabik; Maria Szczepańska (MDPI AG, 2023)
Background: IgA-associated vasculitis (IgAV), formerly known as Henoch-Schönlein purpura (HSP) disease, is the most common type of systemic vasculitis observed during developmental age. Available published studies associate the outbreak of the disease with streptococci, adenovirus, parvovirus, mycoplasma, respiratory syncytial virus (RSV), and influenza infection in approximately 50% of patients with HSP, while some emerging reports have described a few cases of COVID-19 infection being associated with HSP in both adults and children. Case presentation: a 7-year-old girl was diagnosed with HSP, fulfilling the four required clinical criteria (palpable purpura and abdominal pain, arthralgia and edema, and periodic renal involvement). Infection with SARS-CoV-2 was confirmed via the presence of IgM and IgG antibodies. The disclosure of the Henoch-Schönlein purpura (HSP) disease was preceded by a mild, symptomatically treated infection of the upper respiratory tract. High levels of inflammatory markers were observed during hospitalization, including leukocytosis, an increased neutrophil count and a high neutrophil-to-lymphocyte ratio (NLR). All of these markers are associated with IgAV gastrointestinal bleeding, which was also associated with rotavirus diarrhea observed in the patient. Conclusions: This case presented by us and similar cases presented by other authors indicate the possible role of SARS-CoV-2 in the development of HSP, but this assumption requires further research and evidence-based verification.